Upaya Komprehensif Mengendalikan Masalah Kesehatan Lansia Melalui Skrining PTM dan Senam Lansia - Intan Kumalasari; Maksuk Maksuk; Syarif Burhan Yusuf; M Rajab Alfariz; Miranda Salsabila Nur Suryani; Anisa Kurniawati; Mardanila Mardanila (Universitas Muhammadiyah Manado, 2024)
Non-communicable diseases (NCDs), such as hypertension and diabetes, are the leading causes of death among the elderly in Indonesia. To address this issue, a community service program was conducted in the working area of the Ariodilla Health Center, Palembang, focusing on NCD screening and health education through senior exercise. The program was attended by 45 elderly individuals who underwent health screenings, including blood pressure, blood sugar, cholesterol, and uric acid measurements. The results showed that 15.5% of the elderly were diagnosed with diabetes mellitus, 75.8% had high cholesterol, and 24.4% had elevated uric acid levels. In addition, senior exercise sessions were conducted to improve physical fitness. This program successfully increased the knowledge and awareness of the elderly regarding NCDs, the importance of regular health check-ups, and maintaining a healthy lifestyle. In the future, similar programs are expected to be expanded to reach more elderly individuals, aiming to prevent serious complications from NCDs.